Chestnut tannins in broiler diets: Affecting intestinal development in different feeding phases - Buyse, Kobe; Noten, Noémie Van; Delezie, Evelyne; Goethals, Luc; Janssens, Geert P. J.; Lourenço, Marta (Frontiers in Veterinary Science, 2022)
It is known that high doses of various tannins could impair broiler growth, and this seems to be linked to a lowered protein availability. However, effects on protein digestion under the influence of hydrolysable tannins were minimal in previous research and literature. Other possible proposed reasons to explain reduced growth are scarce. In this experiment we studied the effect of hydrolysable tannins on body allometry by using different feeding schemes throughout the rearing period. In total 112 individually reared male Ross 308 broilers received a 3-phase basal diet with chestnut wood extract (+: 2,000 mg/kg) or not (–: 0 mg/kg) (Tanno-SAN®, Sanluc International NV, Belgium). This resulted in 2 groups during the starter period (S+, S–), 4 groups in the grower period (G++, G+−, G–+, G–) and 8 groups in the finisher period (F+++, F++−, F+−+, F+−−, F−++, F−+−, F−−+, F——). Similar to previous studies, growth reduction was also observed in this study. Effects were the largest in broilers that were given the tannins during the grower phase. At the end of each phase 8 broilers per group were euthanized and sampled. Liver, pancreas, pectoralis muscle, intestinal weights and intestinal length were recorded. The largest effects were seen on the intestine. Broilers that received tannins during the grower phase, had longer intestines at the end of the finisher period. Furthermore, histological differences between treatment groups were observed at the end of the grower period. Addition of tannins in the grower phase (G–+, G++) resulted in longer villi, whereas addition of tannins in the starter (G+−, G++) caused deeper crypts at the end of the grower phase, with the group (G–+) having the highest villi-to-crypt ratio. These results tentatively prove that tannins influence intestinal growth, both macroscopically as well as histologically. We hypothesize that the observed growth reduction with tannins could be the result of a changed energy and nutrient partitioning, i.e., more nutrients are directed to intestinal growth than for muscle growth.